A Long‐Lasting Auroral Spiral Rotating Around Saturn's Pole. Issue 23 (7th December 2020) - Palmaerts, B.; Yao, Z. H.; Sergis, N.; Guo, R. L.; Grodent, D.; Dialynas, K.; Gérard, J.‐C.; Mitchell, D. G.
Abstract: The main ultraviolet auroral emission at Saturn consists of multiple structures forming a discontinuous ring of emission around the poles, occasionally organized in a global spiral. We present continuous observation of an auroral spiral rotating at ∼85% of rigid corotation during several hours. Simultaneously, energetic neutral atom (ENA) emissions revealed a hot magnetospheric plasma population located in the same local time sector as the ends of the rotating spiral. Following plasma theory, we propose that pressure gradients induced by the energized plasma distorted the magnetospheric current system, resulting in the spiral morphology of the aurora. The rotating hot plasma was several times reenergized in the dusk sector during at least 2 days, generating a long‐lasting auroral spiral. The ultraviolet spiral, the ENA emissions, and the ions revealed by this multi‐instrument data set are three signatures of a magnetosphere‐ionosphere coupling current system and of the associated hot plasma population rotating around Saturn. Key Points: The main auroral emission forms a spiral observed during two consecutive days The spiral morphology is due to the presence of a hot plasma population in the magnetodisc The auroral spiral winds while the hot plasma bubble expands due to gradient and curvature drifts